VOLTAGE ANNUNCIATOR AS SECURITY-ENHANCING FACILITY - Yury Ivanovich Zharkov; Stanislav Dmitriyevich Mrykhin; Dmitry Stanislavovich Mrykhin; Evgeny Petrovich Figurnov (Advanced Engineering Research)
The remote voltage annunciator – the device developed for detecting dangerous voltage at the specific workplace, in the high voltage supply units, in the electric traction networks, and catenaries – is described. The remote voltage annunciator scheme for the high-voltage AC-operated equipment is described. The annunciator needs no battery power supply block, is easy-to-use, and allows noncontacting detecting dangerous voltage, checking and detecting a high and dangerous voltage cable, determining residual and induced voltage. The remote annunciator uses the antenna designed to detect the radiated electrical field in the energized conductors. The electric radiation increases with the voltage growth, but lowers with the distance increase. When an electrical field is detected, or there is some motion towards the high-voltage current-carrying device, the annunciator starts to perform sound and light alarms.